Applications of Photocatalytic Disinfection - Joanne Gamage; Zisheng Zhang (International Journal of Photoenergy)
Due to the superior ability of photocatalysis to inactivate a wide range of harmful microorganisms, it is being examined as a viable alternative to traditional disinfection methods such as chlorination, which can produce harmful byproducts. Photocatalysis is a versatile and effective process that can be adapted for use in many applications for disinfection in both air and water matrices. Additionally, photocatalytic surfaces are being developed and tested for use in the context of “self-disinfecting” materials. Studies on the photocatalytic technique for disinfection demonstrate this process to have potential for widespread applications in indoor air and environmental health, biological, and medical applications, laboratory and hospital applications, pharmaceutical and food industry, plant protection applications, wastewater and effluents treatment, and drinking water disinfection. Studies on photocatalytic disinfection using a variety of techniques and test organisms are reviewed, with an emphasis on the end-use application of developed technologies and methods.